DEVELOPMENT OF NONWOVEN FABRIC USING TEXTILE WASTE AND ITS CHARACTERIZATION - MINAKSHI HAZARIKA; BINITA B KALITA (The Journal of Research ANGRAU, 2024)
The study was conducted during the year 2021. Textile waste fibers are a significantly byproduct of the fashion and textile industries, stemming from various stages of production, consumption and disposal. These fibers include leftover fabric scraps, trimmings and postconsumer garments that are discarded. With the rise of fast fashion and increased consumption, textile waste has become a pressing environmental concern globally. These waste fibers contribute to landfills, water pollution and greenhouse gas emissions. Finding sustainable solutions for managing and repurposing textile waste fibers is crucial for mitigating their environmental impact and promoting circularity within the textile industry. About 5.8 million tons of textile waste are generated every year whereas only 1.5 million tons of such textiles waste are recycled by industrial and tailoring enterprises. This has led the investigator to select one such waste that could be explored for the present study. Therefore, tailor discards were considered along with Kapok which has good conductivity and also has good insulation for both thermal and acoustic properties because of its hollow nature and light weight. The study was carried out by blending wool and Kapok with three blending ratios of wool 100%, kapok 100% and wool kapok (50:50%) to form nonwoven sheets and the properties of the sheets were investigated.